Three dimensional craniofacial morphometrics: analysis of malay cleft lip and palate infants - Basir, Abdul Hakim Abdul; Rajion, Zainul Ahmad (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2005)
Three dimensional craniofacial morphometry was investigated in a sample of 29 cleft lip and palate (CLP) infants aged between 0-12 months. They were compared with 12 non-cleft (NC) infants in the same age group. Every one of them undeiWent CT scan procedure to obtain three dimensional data. This data was then measured in PERSONA software, developed by the Australian Craniofacial Unit, Adelaide. Significant differences in the craniofacial-cervical morphology of infants with CLP compared with NC infants were noted as well as the differences between affected males and females. However these differences need to be further recognized in the future since they can improve our understanding of developmental associations in CLP and also assist in the management of individuals with CLP .